Effect of the preparation method of control samples on external quality assessment results of PSA testing - Bartos, Vladimir; Stern, Petr; Zavada, Milan; Gartnarova, Marcela; Safarcik, Kristian (Anticancer research, 2003)
BACKGROUND: The control of PSA tests is included in most systems of External Quality Assessment (EQA). As part of the preparation of control samples, seminal fluid is sometimes used to increase the level of PSA. MATERIAL AND METHODS: In two separate studies, the effect of the method of preparation of control samples was evaluated. The first study, carried out under the conditions of EQA of PSA examination, assessed the results of the analysis of samples prepared using seminal fluid and samples prepared using the addition of human serum. The second study analysed two groups of samples (sera and control samples to which seminal fluid was added) using two systems (IRMA and IMMULITE). RESULTS: The fPSA/tPSA ratio in the control samples prepared using the seminal fluid is very high (over 60%) and does not correspond to the usual values. The use of these samples resulted, when compared with the samples prepared using the addition of serum, in a substantial deterioration of inter-laboratory reproducibility of the results in EQA. The differences were most obvious when the results of individual analytical systems were compared, particularly for the examination of fPSA. CONCLUSION: The use of seminal fluid for the preparation of control samples is not appropriate.
Keywords: luminiscenční měření; sperma; Electrochemistry; Luminescent Measurements; Humans; elektrochemie; referenční standardy; řízení kvality; Immunoenzyme Techniques; Prostate-Specific Antigen; lidé; Radioimmunoassay; radioimunoanalýza; reprodukovatelnost výsledků; Reference Standards; imunoenzymatické techniky; Quality Control; Male; Reproducibility of Results; Immunoassay; prostatický specifický antigen; Semen; mužské pohlaví; imunoanalýza